Implementation of Law Number 23 of 2011 On the Use of Zakat Funds for the Productive Economic Program of Dompet Dhuafa Waspada North Sumatra - Rizki Juliana; Abd Rahman Harahap (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Dompet Dhuafa Waspada North Sumatra is one of the zakat collection institutions that implements productive economic programs based on zakat funds. However, in its implementation, the productive economic program still faces several problems in the field. This study aims to analyze the implementation of Law Number 23 of 2011 on the use of zakat funds for productive economic programs at Dompet Dhuafa Waspada North Sumatra. This study uses an empirical juridical method with a sociological approach and a statute approach. Data were obtained through interviews and documentation studies. Then, the data were analyzed qualitatively with deductive reasoning. The results of the study indicate that the implementation of the use of zakat funds for productive economic programs at Dompet Dhuafa Waspada North Sumatra has not been running optimally in accordance with the mandate of Law Number 23 of 2011. This condition is evident from the unfulfilled principles of equality, justice, and territoriality, as well as the suboptimal functions of planning, mentoring, and program supervision. The main problems lie in the management aspect of the program, namely limited program distribution, limited funding, minimal variety of productive business types, suboptimal mentoring and supervision, and low managerial skills and financial literacy among mustahik. Therefore, strengthening planning, mentoring, supervision, and institutional synergy is needed so that productive zakat management can encourage the economic independence of mustahik and achieve the goals of social justice and welfare.